(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Forward Head Posture (FHP) has become increasingly prevalent among students due to prolonged use of digital devices and visually demanding tasks. Ocular disturbances such as myopia and blurred vision often lead to compensatory head-neck adjustments , potentially contributing to FHP. However, there is limited evidence on the association between ocular disorders and FHP among undergraduate students, particularly in Pakistan. Objective: To determine the prevalence of Forward Head Posture among undergraduate students with ocular disorders and evaluate the association between ocular disorders and craniovertebral angle (CVA). Methods: A cross-sectional study was conducted among 377 undergraduate students recruited through non-probability purposive sampling from public and private universities in Peshawar. Data were collected using the Nomophobia Questionnaire (NMP-Q), Neck Disability Index (NDI), and photogrammetric measurement of CVA. Ocular disturbances were self-reported. Statistical analyses, including descriptive statistics and the Chi-square test, were performed using SPSS version 25. Results: A high prevalence of FHP was observed, with 31.0% having mild FHP, 26.5% moderate FHP, and 10.6% severe FHP. Blurred vision (35.8%) and myopia (24.7%) were the most common ocular disturbances reported. A statistically significant association was found between ocular disturbances and CVA categories (p = 0.004). Additionally, 86.5% of participants reported neck pain, and 95.5% reported upper back pain, both correlating with increasing FHP severity. Conclusion: The findings suggest a significant association between ocular disturbances and FHP among undergraduate students. The prolonged use of digital devices and visual impairments like myopia and blurred vision contribute to the development of FHP.